If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+4x=10x-6
We move all terms to the left:
7+4x-(10x-6)=0
We get rid of parentheses
4x-10x+6+7=0
We add all the numbers together, and all the variables
-6x+13=0
We move all terms containing x to the left, all other terms to the right
-6x=-13
x=-13/-6
x=2+1/6
| 3x-4(-3x-6)=-66 | | 2/3x-1=-1/3x-7 | | 4=(-0.8)x | | 6=m-7÷8 | | -v+5+6v=1+5v+3= | | 6=m-7^8 | | 65+34=45x+73-83x | | 6q-348=6(2-5q)-4q | | 3x+7(-7x-20)=90 | | 3(d-6)=3 | | (-1+8x)+46=18x+5 | | r-11÷11=-10÷11 | | 7(1+x)=6(5+x) | | 28x^2+24x+9=0 | | -17+13x=13x-17 | | c=5/9-(F-32) | | 1/9w-6=7/9 | | 7x+20=0 | | -7x+3(3x-7)=3 | | 5-3x=x+11 | | 13x-29=7 | | 9/5y=-10 | | 7x-7=-3x-7 | | d-12=19d-12=19 | | 18x+3=3(6x-12) | | -2(6y-2)+9y=1+3(2y-1) | | -8(3x-1÷4)=2(9-7x) | | 5(4-2x)=8 | | 46=9r-8 | | -4(-4x-6)-7x=6(2x+7) | | –12x+4=–32 | | -3(6x-4)+6x=-3(x+1) |